Beiträge zur Collembolenfauna Israels. - Palissa, Alfred (Contributions to Entomology = Beiträge zur Entomologie, 2006)
A collection of 233 samples of Collembola was examined, collected between 1976-1988 in Israel. All samples are from moist habitats. 1182 individuals were determined as 61 species, 3 of them new to science: Neonaphorura ortali n. sp., Proisotoma judeana n. sp. and Prodrepanura pseudomusatica n. sp. 29 species are recorded for the first time in Israel. Most are Palaearctic or cosmopolitan species. Some previously known from Mediterranean countries are now also recorded in Israel: Acherontiella bougisi, Neanura granulata, Protanura quadrioculata, Anurophorus coiffaiti, Heteromurus major, H. tetrophthalmus, Arrhopalites jeanelli, Deuterosminthurus sulfureus mediterraneus. Particularly remarkable is Crytopygus womersleyi. This species was so-far only known from Australia. At present 128 species of Collembola are known from Israel. - A survey of the geographical regions of Israel shows the highest number of species and individuals in the Golan Heights (northern Israel) and the Judean Mountains (Central Israel). Only few Collembola were found in the southern regions of Israel (northern, central and southern Negev). Although the samples are not directly comparable, a distinct north-south decline in species numbers is apparent, corresponding with climatic factors. Only Prodrepanura pseudomusatica n. sp. occurred in areas 16 B (Hiyyon - paran area) and 17 B (Negev mountain). Nomenclatural Acts ortali Palissa, 2006 (Neonaphorura), spec. n. pseudomusatica Palissa, 2006 (Prodrepanura), spec. n. judeana Palissa, 2006 (Proisotoma), spec. n.